The protective effect of biologic and targeted-synthetic therapies on developing multisystem inflammatory syndrome in children - Lana Khoury; Adi Miller-Barmak; Adi Miller-Barmak; Shereen Shehadeh; Shereen Shehadeh; Shereen Shehadeh; Hilla Cohen; Dana Hadar; Mohamad Hamad Saied; Mohamad Hamad Saied; Mohamad Hamad Saied (Frontiers in Pediatrics, 2025)
BackgroundMultisystem Inflammatory Syndrome in Children (MIS-C) is a severe, life threatening, complication that arises weeks after acute Coronavirus disease 2019 (COVID-19) infection, often presenting with fever and diverse systemic symptoms. Limited data exists on the effectiveness of biologic and targeted-synthetic therapies in preventing MIS-C development. Therefore, our aim was to investigate whether biologic and targeted-synthetic therapies can prevent the occurrence of MIS-C.MethodsWe assessed the Clalit Health Services database, the largest health care organization in Israel, data from 793,909 children aged 0–18 years who tested positive for COVID-19 were analyzed. The diagnosis of MIS-C was adjudicated using the case definition used by the Centers for Disease Control and Prevention (CDC) or by the World Health Organization (WHO). Patients receiving biologic and targeted-synthetic therapies were compared to a control group.ResultsAmong 793,909 cases, 573 children received biologic and targeted-synthetic therapies, and 143 cases of MIS-C were identified. Notably, none of the individuals treated with biologic and targeted-synthetic therapies developed MIS-C.ConclusionOur study highlights our hypothesis on the efficacy of biological treatments in preventing MIS-C. Although statistical significance was not achieved due to the absence of MIS-C cases in patients receiving biologic and targeted-synthetic therapies, our study shows a possible association between biological therapies and reduced risk of MIS-C following COVID-19 infection in children. Further research, including prospective studies with larger cohorts, is warranted to confirm these findings and elucidate underlying mechanisms.